2008
DOI: 10.1080/10715760801976600
|View full text |Cite
|
Sign up to set email alerts
|

Severe Vitamin E deficiency modulates airway allergic inflammatory responses in the murine asthma model

Abstract: Allergic asthma is a complex immunologically mediated disease associated with increased oxidative stress and altered antioxidant defenses. It was hypothesized that α-tocopherol (α-T) decreases oxidative stress and therefore its absence may influence allergic inflammatory process, a pathobiology known to be accompanied by oxidative stress. Therefore, selected parameters of allergic asthma sensitization and inflammation were evaluated following ovalbumin sensitization and re-challenge of α-T transfer protein (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 63 publications
(99 reference statements)
4
19
0
Order By: Relevance
“…In a recent study, a systematically review revealed the associations between inflammatory responses and asthma severity in pediatric asthma, which indicated that IFN-γ, IL-10 and IL-17 may serve as prognostic indicators of pediatric asthma (34). In addition, various strategies targeting inflammatory responses to improve airway remodeling in asthma physiopathology have been investigated, and the results of these studies support the hypothesis that modulating the allergic inflammation improved asthma physiopathology in patients with asthma in animals model and clinical trials (35)(36)(37)(38). Furthermore, previous reports have indicated that the pathogenesis of airway inflammation in asthma patients may be associated with the normal function and maintenance of the airway smooth muscle cells (39)(40)(41).…”
Section: Discussionsupporting
confidence: 52%
“…In a recent study, a systematically review revealed the associations between inflammatory responses and asthma severity in pediatric asthma, which indicated that IFN-γ, IL-10 and IL-17 may serve as prognostic indicators of pediatric asthma (34). In addition, various strategies targeting inflammatory responses to improve airway remodeling in asthma physiopathology have been investigated, and the results of these studies support the hypothesis that modulating the allergic inflammation improved asthma physiopathology in patients with asthma in animals model and clinical trials (35)(36)(37)(38). Furthermore, previous reports have indicated that the pathogenesis of airway inflammation in asthma patients may be associated with the normal function and maintenance of the airway smooth muscle cells (39)(40)(41).…”
Section: Discussionsupporting
confidence: 52%
“…Our interpretation of this study is that high g-tocopherol in the soy oil negated the effect of the a-tocopherol that was administered. Mice deficient in liver a-tocopherol transfer protein (aTTP) exhibit severe deficiency in tissue a-and g-tocopherol as well as reduced IgE after OVA challenge to the lung (35). In these mice, it is not known whether severe tocopherol deficiency during mouse development alters leukocyte hematopoiesis or leukocyte responsiveness.…”
mentioning
confidence: 99%
“…Animal diet and water were provided ad libitum. Allergic asthma sensitization was performed as previously reported in work by Kenyon and colleagues [26,27]. Briefly, mice (6-8 weeks of age) were sensitized via intraperitoneal injection (i.p.)…”
Section: Animals Sensitization and Particle Administrationmentioning
confidence: 99%
“…We have used an ovalbumin sensitization and exposure mouse model of allergic airway inflammation to determine the lung retention and biodistribution of polystyrene nanoparticles (∼100 nm) and compared results to a normal mouse control group. The ovalbumin mouse model is well established in the literature and is commonly used to study asthma [17,26,27]. This model has proven to exhibit key features of asthma, including airway hyperresponsiveness, eosinophilic bronchitis, acute inflammation, increased airway reactivity, and mild airway obstruction [26].…”
Section: Introductionmentioning
confidence: 99%